Mesomechanical numerical modeling of the stress-strain localization and fracture in an aluminum alloy with a composite coating; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Balokhonov R. R. Ruslan Revovich; Schwab E. A. Eugen; Romanova V. A. Varvara Aleksandrovna; Zinoviev A. V. Aleksandr; Martynov S. A. Sergei (2014, 2014)
Title screen